Analyze jitter to improve high-speed design. - Lauterbach, M. (IEEE spectrum)
The authors describe how, in order to overcome timing jitter-the nemesis of high-speed design engineers-its source must be known. They detail how, to divine its source, thousands of signal observations must be collected and scrutinized to uncover flaws